A Newly Discovered Fragment of Dietrich of Freiberg's De origine rerum praedicamentalium - Steel, Carlos (Recherches de théologie et philosophie médiévales, 2024)
A manuscript fragment recently acquired by the Leuven University Library consists of two sections from Dietrich of Freiberg’s De origine rerum praedicamentalium. This note briefly presents the Leuven fragment.